The Effect of Endometrial Compaction During the Luteal Phase on Pregnancy Outcomes in Patients Undergoing Intrauterine Insemination - Fulya Cagli; Mehmet Dolanbay; Varol Gulseren; Serhan Kutuk; Savas Karakus; Kemal Erdem Basaran; Ercan Aygen (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: Compression/thinning of the endometrial thickness with the effect of progesterone during the luteal phase of the menstrual cycle is defined as endometrial compaction. This study aimed to show the effect of changes in endometrial thickness in the luteal phase of intrauterine insemination cycles on pregnancy outcomes.